Pengaruh Kompetensi dan Etos Kerja terhadap Kinerja Pegawai Pengadilan Negeri Sidikalang - Simamora Intan Cahaya Beta; Rifqah Harahap; Maduma Sari Sagala (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
The problem in this study is employee performance at the Sidikalang District Court, where performance is suboptimal, and there are indications of a lack of work ethic and competence in several aspects. The purpose of this study is to determine the influence of competence and work ethic on employee performance at the Sidikalang District Court. This study used quantitative methods. The population and sample were 35 employees at the Sidikalang District Court. Sampling was conducted using a saturated sampling technique. Data sources in this study were primary and secondary data. Data collection methods in this study included observation, interviews, questionnaires, and documentation. Data analysis used multiple linear regression, with hypothesis testing (partial test, simultaneous test, coefficient of determination test) at the Sidikalang District Court. Data processing was performed using SPSS version 25. The results of the multiple linear regression test are Y = 1.332 + 0.415X1 + 0.345X2 + e which shows that competence and work ethic will improve employee performance. The results of the partial test (t-test) show that competence has a positive and significant effect on employee performance where it can be seen t count = 3.057> t table 2.036. And the work ethic variable also has a positive and significant effect on employee performance where it can be seen = 2.605> t table 2.036. The results of the simultaneous test (F test) can be seen the F count value = 96.771> t table 3.29, meaning that together competence and work ethic have a positive and significant effect on employee performance. The results of the determination coefficient with a correlation regression value of 0.849 (84,90%), so it can be said that 84,90 % of the variation of the independent variables, namely competence and work ethic in the model, explains the employee performance variable at the Sidikalang District Court while the remaining 15,1% is explained by other variables.